(untitled) (International Journal of Physiotherapy, 2016)
Background: Spasticity is one of the major neurological complications occurring in people with Spinal Cord Lesions due to loss of supra-spinal and spinal control over alpha motor neuron activity. Its accurate assessment is necessary for tailoring patient specific rehabilitation program. Clinical assessment is commonly done through Modified Ashworth Scale where in the examiner subjectively judges resistance to passive range of motion whereas, electrophysiological quantification of spasticity can be done through Hoffman’s Reflex which is an estimate of alpha motor neuron activity. Methods: This co-relational study establishes an association between MAS and H reflex in a sample of both traumatic and non-traumatic Spinal Cord lesion patients. A sample of 22 patients was obtained who were rated for MAS grades 0,1,1+,2 and 3 in bilateral gastro soleus and consequent H reflex elicitation was done. Results: Karl Pearson Correlation coefficient was calculated between MAS and H amplitude (r = 0.342, p<0.05); MAS and h latency (r = 0.013, p>0.05) ; MAS and H/M ratio (r=0.190 ,p>0.05). Conclusion: It was concluded that there exists a weak but significant correlation between MAS and H amplitude but non-significant relationship between MAS and H latency; MAS and H/M ratio.